The rape of Nanking - Hudson, Peter; Mori, Jun.; Viallet, Serge; ARTE France; Films for the Humanities (Firm); Point du Jour (Firm) (Princeton, NJ : Films for the Humanities & Sciences, 2007)
Over the course of six weeks in 1937-38, Imperial Japanese forces massacred hundreds of thousands of Chinese civilians and prisoners of war as the Empire of the Sun turned Nanking into a veritable hell on earth. This program seeks both to expose and to understand that shocking outrage against humanity through the testimonies of the last surviving Japanese veterans and the recollections of Chinese eye witnesses. Rarely seen newsreel and amateur footage, uncensored personal photos and excerpts from diaries are interspersed throughout.
This disc is a DVD-R and may fail to play on some DVD equipment.
Narrator, Peter Hudson ; photography, Serge Viallet, Jerome Lafon ; editor, Alexandre Auque ; music, Niels Poux.
Narrator, Peter Hudson.
DVD-R.
Keywords: Nanking Massacre, Nanjing, Jiangsu Sheng, China, 1937.; Sino-Japanese War, 1937-1945 -- Atrocities; Nanjing (Jiangsu Sheng, China) -- History; Documentary films